Synchronization of Two Identical Restricted Planar Isosceles Three-Body-Problem and a Study on Possible Chaos Control - Khan, Ayub; Pal, Rimpi (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we have investigated Complete Synchronization, Anti- Synchronization and all possible cases of Hybrid Synchronization of two restricted planar isosceles three-body-problem evolving from different initial conditions using Active Control Technique. Further, the possible role of control functions in the control of Chaos is analyzed. Finally, numerical simulations are performed to illustrate the effectiveness of the proposed control techniques.